El proceso populista : momento, fenómeno, régimen : el caso que no fue : Chile (1932-1973) - Riveros Ferrada, Claudio (Serie Historia y ciencias sociales., 2018)
In this book, populism is conceived as a historical process that obeys different conditions of possibility. It is argued that any populist process requires both a discursive articulation and a deep mobilization in a context of hegemonic crisis. Conceptually this translates into the existence of a moment, phenomenon and a populist regime. This theoretical innovation is applied empirically to Chile, between the years 1932-1973, a country that the academy has considered immune to populism. Indeed, it is about answering, on the one hand, if it is true that populism (as a process) did not occur in Chile and determining, on the other, what was the reason for it. It is argued that such exceptionality had to do, first, with the consolidation of institutional corsets that prevented the triggering of a populist process; and second, because a particular type of democracy was reinforced, which was highly representative as well as markedly tutelary.